Visões de futuro em Freire e Dewey: perspectivas interculturais das matrizes (pós)coloniais das Américas - Maria Manuela Duarte Guilherme (EccoS – Revista Científica)
This article offers a comparative analysis of John Dewey’s and Paulo Freire’s visions of the future, as a fundamental legacy of their work, having in mind the different cultural and epistemological environments that constituted the intellectual backdrop and socio-historical baggage of their works. Their visions of the future are here also approached from an intercultural perspective within the framework of two different (post)colonial matrices embodied by North and South Americas. This article attempts to unveil the underlying historical, political and social substrata influencing the form and essence of the rhetoric and ideology of such conceptual and academic frameworks of reference in the field of education and pedagogy in the 20th century. Finally, the valuable theoretical-practical legacies of both philosophers of education are here emphasized for the purpose of an idea of future in the educational policies and pedagogical practices of cosmopolitan societies of the 21st century.